Menebar Batu Meraup Rupiah: Eksistensi Pedagang Batu Akik di Kota Kendari - Hasniah .; Alham Haidir Darmin (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2015)
This study aimed to identify and describe the existence of agate traders in the courtyard of ex MTQ Kendari and strategy of agate traders in maintaining their business in the courtyard of ex MTQ Kendari. This study used the theory of Capital by Pierre Bourdieu and the method used Ethnography method with data collection was done through observation techniques and in-depth interview, meanwhile the selection of informant was using purposive sampling technique. Data were analyzed by descriptive qualitative, data analysis was intended to simplify the data obtained into a form that was easier to read and interpret. The results showed that the existence of agate traders could be viewed by two aspects, namely the goods and services offered. As for the aspects of the goods offered by agate traders were selling agate, selling agate beads, selling ready-made agate ring and aspects of the services were offering services of agate crafts. While the strategy used by agate traders in the courtyard of the ex MTQ Kendari in maintaining their business was namely choosing a strategic location shanties, lowering the price of agate, establishing cooperation among agate traders, selling online, accepting agates’ orders and making contests / competitions of agate. Therefore, this study recommended to several parties such as for the traders; complied with applicable rules in carrying out their trade activities meanwhile for the government of Kendari; to regulate / control and determine agate trade area that would be easily to access by the buyer. Keywords: agate traders, attention and existence strategy